1984
DOI: 10.1007/bf02678796
|View full text |Cite
|
Sign up to set email alerts
|

Cationic surfactants in laundry detergents and laundry aftertreatment aids

Abstract: Cationic surfactants have a positively charged nitrogen atom and at least one hydrophobic, long-chain substitucnt in the molecule. Because of their fabric-softening and antistatic properties, they are used as active materials in fabric-softening agents. Suitable cationic surfactants are mostly quaternary ammonium salts, and to a lesser extent, imidazolinium salts with two long hydrophobic alkyl chains. Alkylated, partly cthoxylated polyamincs, amine amities, ester amines and di-quaternary compounds also have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 31 publications
0
24
0
3
Order By: Relevance
“…Several thousand patents have been filed in the last 30 yr covering variations and combinations of new and old molecules as well as formulations of softener actives with different cosurfactants and functional additives (3,5,18,22,49). In practice, the mole-cules described earlier represent probably 99% of the cationic actives being used in rinse-added fabric softeners around the world today as a result of their ability to meet regional performance requirements (Table 4).…”
Section: Fabric Softener Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several thousand patents have been filed in the last 30 yr covering variations and combinations of new and old molecules as well as formulations of softener actives with different cosurfactants and functional additives (3,5,18,22,49). In practice, the mole-cules described earlier represent probably 99% of the cationic actives being used in rinse-added fabric softeners around the world today as a result of their ability to meet regional performance requirements (Table 4).…”
Section: Fabric Softener Moleculesmentioning
confidence: 99%
“…They provide a renewable finish that interferes only minimally with the laundering process. They are based on low-cost raw materials, predominantly tallow, lard, or, alternatively, on seed oils such as palm oil, soybean, or canola (rapeseed) oil (18). They are relatively easy to formulate with conventional mixing equipment and require few supplemental ingredients.…”
mentioning
confidence: 99%
“…Previous reports indicated that a temperature rise increases quaternary ammonium salt adsorption on cellulose (18). The temperature used in our present work was the same in all the experiments because the purpose was to simulate the conditions used in the paper industry.…”
Section: Resultsmentioning
confidence: 96%
“…It is prequiste for the softening and antistatic effect of cationic surfactants (imidazoline), that they are absorbed on the textile substrates [37][38][39][40][41] . A high degree of subtantivity between the negatively charged textile surfaces and the positively charged part of the cationic surfactants (imidazoline) molecules in the aqueous phase exists ( ) under the condition of rinse bath, for intance, wool or cotton absorb more than 90% of the quaternary ammonium derivative of imidazoline compounds from the aqueous phase.…”
Section: Mode Of the Action Of Imidazolinementioning
confidence: 99%
“…Several thousands patents have been filed in the last 30 years covering variation and combinations of new and old molecules as well as formations of softeners actives with different cosurfactants and functional additives [4][5][6][7][8] . In practice, the molecules DHTDMAC, diamidoamine, imidazoline and esterquats are probably 99% of the cationic actives being used in rinse added fabric softeners around the world today as a result of their ability to meet regional performance requirement.…”
Section: Introductionmentioning
confidence: 99%